Network pharmacology and experimental validation to elucidate the pharmacological mechanisms of OATF against kidney stones - Dai, Sisi; Fang, Qi; Li, Hong-Yan; Sun, Rui; Zhang, Hui-Yong; Wu, Wei (Frontiers in Pharmacology, 2025)
IntroductionOrthosiphon aristatus (Blume) Miq. (OA) is widely used in folk medicine to treat kidney stones (KS). Its total flavonoids (OATF) are the primary active constituents responsible for its therapeutic effects. However, the exact mechanism of action (MOA) remains unclear. This study aimed to investigate the pharmacological activity of OATF against KS and elucidate its underlying MOA.MethodsNetwork pharmacology and molecular docking were utilized to predict the potential targets and pathways of OATF. An animal model of calcium oxalate crystal deposition was created using intraperitoneal injections of ethylene glycol (EG) and ammonium chloride (AC), alongside a model using human renal tubular epithelial cells (HK-2) induced by supersaturated oxalate (Ox) to investigate the pharmacological mechanisms of OATF against oxidative stress and apoptosis. The effects of OATF on crystal deposition and renal damage were assessed using hematoxylin-eosin (H&E) and periodic acid-Schiff (PAS) staining. Renal tubular damage and apoptosis were evaluated via TUNEL staining. The MOA was explored using Western blotting analyses.ResultsNetwork pharmacological analysis identified the EGFR/PI3K/AKT pathway as a key mechanism in KS. In vitro experimental results demonstrated that OATF effectively protected HK-2 cells from oxidative stress, inhibited calcium oxalate crystal adhesion, and reduced apoptosis. In vivo, OATF significantly decreased serum creatinine (SCR), serum calcium (Ca), serum phosphorus (P), and blood urea nitrogen (BUN) levels in CaOx-induced Sprague-Dawley (SD) rats, indicating its protective effects against KS.ConclusionOATF effectively inhibited kidney stone formation and mitigated renal injury by attenuating oxidative stress and apoptosis through activation of the EGFR/PI3K/AKT pathway. These findings highlight OATF’s therapeutic potential for KS management and provide a scientific basis for its traditional use in herbal medicine.